CARACTERIZAÇÃO DA MATÉRIA ORGÂNICA OXIDÁVEL DO SOLO EM DIFERENTES FRAGMENTOS FLORESTAIS DE MATA ATLÂNTICA - BISPO, Luan Soares; ROSSET, Jean Sérgio; OZÓRIO, Jefferson Matheus Barros; SOUZA, Camila Beatriz da Silva; CASTILHO, Selene Cristina de Pierri; MARRA, Leandro Marciano (ANAIS DO ENIC, 2018)
-